The Effect of Using the Reading, Questioning, and Answering (RQA) Assistance of the Quizizz Media Learning Model on the Science Literature Ability of Students - Andi Badli Rompegading; Liska Syam; Muhammad Nasir (Postgraduate, University of Mataram, 2022)
This study aims to determine the effect of using the Reading, Questioning, And Answering (RQA) Learning Model Assisted by Quizizz Media on the Scientific Literacy Ability of Class XI MIPA Students at SMA Negeri 3 Wajo. This research was conducted at SMA Negeri 3 Wajo. This research method is a quasi-experimental design with a pretest-posttest control group design. The sample taken is class XI MIPA SMA Negeri 3 Wajo, more precisely class XI MIPA 2 and class XI MIPA 3 with a total of 50 students as experimental class XI MIPA 2. Based on the data analysis, the student’s cognitive learning outcomes for the reproductive system material were obtained. The results of the hypothesis on post-test data show that data processing uses hypothesis testing (t-test) using the EXCEL program which obtains values ​​(sig.2-tailed) with a significant level of 5% (0.05). The results of testing the hypothesis (t-test) show the final result that H0 is rejected and H1 is accepted. The average student learning outcomes using the Quizizz learning media are higher.